2021
DOI: 10.1007/s41109-021-00351-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of effective spreaders in contact networks using dynamical influence

Abstract: Contact networks provide insights on disease spread due to the duration of close proximity interactions. For systems governed by consensus dynamics, network structure is key to optimising the spread of information. For disease spread over contact networks, the structure would be expected to be similarly influential. However, metrics that are essentially agnostic to the network’s structure, such as weighted degree (strength) centrality and its variants, perform near-optimally in selecting effective spreaders. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Data transfer is a spreading process that can be represented by a network in order to detect the relative influence of nodes [3]. A network of averaged contacts over time, enables the network's adjacency matrix to provide insights into the major pathways for spread, as in [2] for the identification of influential disease spreaders. For space system flow networks, where targets are sources of data and ground stations are sinks, the eigenvectors of the adjacency matrix can detail the relative influence of ground stations in terms of receiving target data.…”
Section: Introductionmentioning
confidence: 99%
“…Data transfer is a spreading process that can be represented by a network in order to detect the relative influence of nodes [3]. A network of averaged contacts over time, enables the network's adjacency matrix to provide insights into the major pathways for spread, as in [2] for the identification of influential disease spreaders. For space system flow networks, where targets are sources of data and ground stations are sinks, the eigenvectors of the adjacency matrix can detail the relative influence of ground stations in terms of receiving target data.…”
Section: Introductionmentioning
confidence: 99%
“…Data transfer is a spreading process that Clark et al (2019) showed can be represented by a network in order to detect the relative influence of nodes. A network of averaged contacts over time enables the network's adjacency matrix to provide insights into the major pathways for spread, where Clark and Macdonald (2021) demonstrated this by identifying influential disease spreaders in contact networks.…”
Section: Introductionmentioning
confidence: 99%